2023
DOI: 10.31486/toj.22.0087
|View full text |Cite
|
Sign up to set email alerts
|

Cooled Radiofrequency Ablation for Intercostal Neuralgia

Abstract: Background: Intercostal neuralgia is pain associated with the intercostal nerves along the rib, chest, and upper abdominal wall. Intercostal neuralgia has various etiologies, and current conventional treatment options include intercostal nerve blocks, nonsteroidal anti-inflammatory drugs, transcutaneous electrical nerve stimulation, topical medications, opioids, tricyclic antidepressants, and anticonvulsants. For a subset of patients, these conventional treatment options provide little relief. Radiofrequency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Despite a potentially promising and precise technique, cryoablation has limited long-term efficacy with variable success in patients' 1year postablation 16,19,20 . Other nonsurgical treatments of intercostal neuralgia have been attempted but likewise with variable success 2,15,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a potentially promising and precise technique, cryoablation has limited long-term efficacy with variable success in patients' 1year postablation 16,19,20 . Other nonsurgical treatments of intercostal neuralgia have been attempted but likewise with variable success 2,15,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…In a case series of two patients with post-surgical intercostal neuralgias, RFA led to a significant improvement in patients’ pain with no procedural complications. 74 In a retrospective series of 18 patients who underwent cryoablation for post-thoracotomy pain syndrome, the authors reported a mean improvement in pain scores of 3.4 points on a 10-point scale following the procedure. 75 No procedural complications were reported.…”
Section: Intercostal Nerve Block and Nerve Ablationmentioning
confidence: 99%